EFFECTIVENESS OF ONLINE LEARNING FOR ENGLISH SUBJECTS DURING THE COVID-19 PANDEMIC - Endang Sri Andayani; Yulianah Yulianah (Research and Development Journal of Education, 2022)
Because to the widespread Covid-19 pandemic, the educational system in schools has been forced to undergo a fundamental shift away from in-person sessions and toward distance learning (online). Without exception, SD Al Ihsan Bojongsari Depok also facilitates online learning through the use of a variety of online tools, such as Schoology, Google Classroom, Google Form, Whatsapp Groups, and other forms of media. The purpose of this research is to determine whether or not studying English-related topics online during the Covid-19 pandemic was beneficial to students' overall academic performance. Methods of qualitative research are utilized in this research approach. According to the findings, the use of online learning through the utilization of online media in English classes taught in sixth grade at SD Al Ihsan Bojongsari Depok can be successfully carried out. This can be seen from the fact that the scores that students obtained while participating in online learning for English subjects are very good. Additionally, lesson plans and the syllabus have been successfully implemented in learning activities, and models and approaches to learning English can be applied in both teaching and learning